2018
DOI: 10.18203/2320-6012.ijrms20180595
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of lipid profile pattern and atherogenic index of plasma (AIP) having type-2 diabetes mellitus in Bangladesh

Abstract: Background: Dyslipidemia has been noted to play an integral role in the pathogenesis and progression of micro and macrovascular complications in Diabetes Mellitus (DM) patients. The study was aimed to evaluate the prevalence and pattern of dyslipidemia and atherogenic index of plasma (AIP) in type 2 diabetes mellitus patients as it has not been reported previously in BangladeshMethods: This cross-sectional study was conducted at Armed Forces Institute of pathology, Bangladesh from November 2016 to October 2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 16 publications
3
6
1
Order By: Relevance
“…The result of this study showed that 47 patients (55.3%) had a high risk of cardiovascular complications based on AIP value. This result is aligned with the previous studies, where 298 patients (99.3%) were found to be at high risk [14].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The result of this study showed that 47 patients (55.3%) had a high risk of cardiovascular complications based on AIP value. This result is aligned with the previous studies, where 298 patients (99.3%) were found to be at high risk [14].…”
Section: Discussionsupporting
confidence: 93%
“…This study shows that a majority of patients (81 people -95.3%) are suffering from dyslipidaemia, and only 4 of them (4.7%) are not. This result is aligned with a previous study that reported 282 patients (94%) were found to have dyslipidaemia, whereas 6% were not [14][15][16]. Several patients experienced an increase of single lipid fraction; however, most of them experienced an increase of multiple lipid fractions.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This parameter can be easily calculated whenever a lipid profile is requested to assess the patient's cardiovascular risk. p = 0.033) was found [16]. They also stated that the effect of sustained hyperglycemia and insulin resistance, which increases lipogenesis -marked by increasing levels of TG along with low levels of HDL-c -could contribute to elevated levels of AIP in patients with diabetes.…”
Section: Discussionmentioning
confidence: 92%